(3CeGdj GdTLQjs - (3jMji Hf GdMSjf Hf ESeGYjd GdTLQj, CHh GdMSf, GdeQTO HGddg , J (B479 (3g` s ((3SYhO Hf GdMSf Hf fGUQ GdYPQi s)
(3ChdgG (B:s
(3GdMOjK GdQGHY eTQai PcQ GdaWQ hUObI GdaWQ heG jJUd HPdc s
(3BNQgG (B:s
(3Bg ef eVLYi aQjOGhMjOkG ahb aQTi ef GdMUi hGdJQGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs